2010
DOI: 10.1177/2150129710388415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Use of Asthma Action Plans and Asthma Exacerbations in Children With Asthma

Abstract: The purpose of this integrative review is to describe and assess current research findings and summarize the relationship between action plans and asthma exacerbations in children with asthma. Medline, CINAHL Plus with full text, PubMed, and Cochrane Library databases were searched as well as bibliographies of included studies. Three hundred eighty-five studies were identified. Thirteen studies were identified meeting inclusion criteria. Eight studies compared asthma action plans (AAPs) with no AAPs. Five stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Children with asthma miss more than 14 million school days per year in the United States and 1 in 6 school‐aged children in southeast (SE) Minnesota have been diagnosed with asthma . In addition to missing school due to asthma, children with asthma often require care or support during school hours.…”
mentioning
confidence: 99%
“…Children with asthma miss more than 14 million school days per year in the United States and 1 in 6 school‐aged children in southeast (SE) Minnesota have been diagnosed with asthma . In addition to missing school due to asthma, children with asthma often require care or support during school hours.…”
mentioning
confidence: 99%
“…Related to this finding, a systematic review of in-home asthma interventions suggested that action plans are mostly beneficial but do not always lead to better outcomes and no sufficient evidence has been found yet that an action plan alone reduced morbidity 12 months later among preschoolers. 17 AAPs usually have a second page listing how to reduce common household triggers; however, follow-up about these triggers and product use with education in the home was missing as an important component in an important medical review of asthma management. 18 One can glimpse what makes an in-home asthma reduction approach work by examining a key set of 8 case studies by the Asthma Regional Council of New England.…”
mentioning
confidence: 99%